(untitled) (Journal of the College of Basic Education, 2023)
A descriptive study, was carried out from March 15th 2004 to April 20th 2006 in all departments to assess waste management in teaching and non-teaching hospitals in Baghdad. Non probability sampling is performed. A purposive sample of (32) managers who were responsible of waste management in hospitals, including (13) teaching hospitals consisting: (5) general hospitals (8) specialized hospitals consisting of all teaching hospitals in city center (urban) and (19) non-teaching hospitals consist of (6) general hospitals (3) of it in district (Rural), (13) specialized hospitals all of in city center.